تحليل المعجم الأكبر لأحمد طه حسين وأحمد عطاء الله: دراسة المعجم الإندونسية -العربية - Zen, Aatina Khairal 'Athiyyah; Cahyani, Raziqa Diah; Kastrawi, Puji; Bahruddin, Uril (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
In its development, there are curricula for writing an Arabic dictionary, which are: a phonetic dictionary, a special alphabetical dictionary, a rhyming dictionary, a general alphabetical dictionary, and a verbal dictionary. Each curriculum has advantages, disadvantages, objectives and segments. It may be difficult for some Arabic language learners to use Arabic dictionaries with their interest. This research aims to observe and analyze the largest Arabic (Indonesian-Arabic) dictionary and all its advantages and shortcomings. In this research, the researchers used a desk research approach with a descriptive approach. Obtaining data from the largest Arabic (Indonesian-Arabic) dictionary by searching for the library’s sources and documents. The Greater Dictionary (Indonesian-Arabic) is a collaborative effort between Ahmed Taha Hussein and Ahmed Ataullah, and they have a different background that distinguishes them from the Greater Dictionary (Indonesian-Arabic), which is: (1) It contains good pictures because it includes pictures in it, (2) It discusses Pronunciation of words from the language and complements their use, (3) The contents of the KABA dictionary are a mixture of language dictionaries and scientific dictionaries (4) and in the introduction it contains information on a brief history of the Arabic language, the history of the Arab world, the West and Indonesia, as well as the larger dictionary cycle (Indonesian-Arabic) (5) In the conclusion or appendix there is an increase in vocabulary. Hence, the results of this research indicate that this dictionary is intended for the academic community, translators, and learners of the Arabic language in particular.